Noncovalent interactions induced self-association in anthraquinone-iron aqueous redox flow batteries. Issue 8 (23rd March 2022) - Xia, Lixing; Zhang, Yujing; Zhang, Heng; Jiang, Shan; Lv, Qianglong; Huo, Wenbo; Chu, Fengming; Wang, Fuzhi; Li, Hui; Tan, Zhan'ao
Abstract : A pH-neutral aqueous anthraquinone-iron flow battery is demonstrated. The self-association of the anthraquinone is realized via noncovalent interactions. Abstract : Due to safety, potentially low-cost and property tunability, aqueous quinone-based redox flow batteries (RFBs) have drawn considerable attention. Herein, an aqueous anthraquinone-metal RFB with an open circuit voltage of 1.19 V is introduced by employing 3-((9, 10-dioxo-9, 10-dihydroanthracene-1-yl)amino)- N, N, N -trimethylpropan-1-aminium chloride (1-DPAQCl) and iron(ii ) chloride with a glycine additive as negative and positive redox-active materials (RAMs), respectively. 1-DPAQCl molecules tend to be bound via noncovalent interactions to form aggregation as the concentration increases. This behavior is confirmed by variable-concentration 1 H nuclear magnetic resonance, 2D nuclear Overhauser effect spectroscopy, gel permeation chromatography and 1 H diffusion ordered spectroscopy. The calculated solvation free energy agrees with this self-association from the perspective of thermodynamics. The RFB at 0.1 M 1-DPAQCl demonstrates stability up to 600 cycles without observing the erosion of the membrane. At a higher concentration (0.5 M), maximum material utilization (51.8%) of 1-DPAQCl is achieved during 150 cycles at 40 mA cm −2 .